AS IMPLICAÇÕES SUBJETIVAS DECORRENTES DA DOENÇA CRÔNICA EM CRIANÇAS. - Dias, Ana M. d. S.; Decian, Cristina; Braga, Fabiano d. S.; Martins, Indiara; Fraporti, Juliane D. (Salão do Conhecimento, 2013)
Resumo